3D printed cylindrical capsules as a Chlorella pyrenoidosa immobilization device for removal of lead ions contamination - Lan, Shuzhen; Xia, Xinshu; Liu, Zhen; Yang, Yujin; Qian, Qingrong; Luo, Yongjin; Chen, Qinghua; Cao, Changlin; Xiao, Liren (Frontiers in Chemistry, 2022)
Immobilization is considered as a promising strategy toward the practical applications of powdered adsorbent. In this study, three dimensional (3 D) printing cylindrical capsules with cross-linked PVA hydrogels membrane in encapsulate Chlorella pyrenoidosa (Cp) were applied for removal of lead ions (lead nitrate). The chemical compositions, hydrogels performance and morphologies of the membranes were determined by Fourier transformed infrared spectroscopy (FTIR), cross-linking degree, swelling degree, membrane flux and Scanning electron microscopy (SEM). It is found that PVA cross-linking structure is successfully synthesized on the surface of capsule body and cap due to the presence of P V A in the filament. The lead ions adsorption capacity related to initial concentration of 50 mg/L in 48 h is reached 75.61%, revealing good removal ability. The lead ions adsorption ratio remains 78.56% after 7 runs of adsorption experiment, indicating the excellent recovering property of the self-floating 3 D printed capsules device.